A market design approach for workers' selection of the National Electoral Institute of Mexico - Cantala, David; Sempere, Jaume (Estudios Económicos de El Colegio de México, 2015)
In this document we propose a model based in matching games to analyze the problem of workers’ selection by the National Electoral Institute of Mexico. After a revision of the theoretically relevant results, an allocation mechanism is proposed to select the workers. This mechanism improves the existing procedure.